2013
DOI: 10.1039/c2cs35385g
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis using multifunctional organosiliceous hybrid materials

Abstract: Organic-inorganic hybrid materials with different levels of structuration and porous hierarchy and one or several types of active sites in the framework can catalyze multistep chemical processes in a one-pot reactor system following a cascade of reaction events. It will show how the different active sites can act in a synergistic or in a consecutive way following a similar functionality model to biological multisite catalysts. Research on this subject for heterogeneous catalysts is still in the beginning stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
144
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 240 publications
(146 citation statements)
references
References 99 publications
1
144
0
1
Order By: Relevance
“…203 This methodology allowed the combination of the functions present both in the inorganic layers from the aluminosilicate precursors and those located in the organic pillars stabilized in the interlayer region from intercalated disilanes, extending largely the catalytic possibilities of these organic-inorganic layered solids to generate multi-functional catalysts. 204 In this sense, Díaz et al showed the possibility to prepare novel families of layered organic-inorganic hybrid materials synthesized by pillaring with disilanes containing amino, thiol, sulphonic, ethylene, viologen or nitroaniline compounds which were intercalated and stabilized between magadiite layers. Specifically, bridged silsesquioxanes reacted with the surface silanol groups of the inorganic layers of silicate, bonding covalently with them.…”
Section: -Other Lamellar Materials: Hybrid Organic-inorganic Layeredmentioning
confidence: 99%
“…203 This methodology allowed the combination of the functions present both in the inorganic layers from the aluminosilicate precursors and those located in the organic pillars stabilized in the interlayer region from intercalated disilanes, extending largely the catalytic possibilities of these organic-inorganic layered solids to generate multi-functional catalysts. 204 In this sense, Díaz et al showed the possibility to prepare novel families of layered organic-inorganic hybrid materials synthesized by pillaring with disilanes containing amino, thiol, sulphonic, ethylene, viologen or nitroaniline compounds which were intercalated and stabilized between magadiite layers. Specifically, bridged silsesquioxanes reacted with the surface silanol groups of the inorganic layers of silicate, bonding covalently with them.…”
Section: -Other Lamellar Materials: Hybrid Organic-inorganic Layeredmentioning
confidence: 99%
“…Several applications have been developed in catalyses, separation, sensors, solar cells, etc. 16,17 . In recent years, mesoporous materials have been used as the support of noble metal eg.…”
Section: Etcmentioning
confidence: 99%
“…5 discussed the history of the discovery and development of PMOs, emphasizing the most important advances regarding their compositions and structures, morphologies and properties. Later, Fröba and co-workers, 8 Jaroniec, 9 Inagaki and co-workers, 6 Fujita and Inagaki, 7 Lin and co-workers, 10 Ozin and co-workers 11 and Corma and co-workers 12 published some excellent reviews of PMO studies. The most recent review paper was by Van Der Voort and co-workers, 13 who provided a comprehensive overview of these materials, discussing their functionalities, morphology and applications by referring to approximately 300 works on PMO materials.…”
Section: Introductionmentioning
confidence: 99%